2018
DOI: 10.1053/j.ajkd.2018.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoffs in Vascular Access Selection in Elderly Patients Initiating Hemodialysis With a Catheter

Abstract: In elderly hemodialysis patients initiating hemodialysis therapy with a catheter, the optimal vascular access selection depends on tradeoffs between shorter catheter dependence and less frequent interventions to make the vascular access (AVG) functional versus longer access patency and fewer interventions after successful use of the vascular access (AVF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
65
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 37 publications
1
65
1
Order By: Relevance
“…In other work, 2 we found that while vascular access events preceding successful use favor AV grafts, those occurring after successful use favor AV fistulas. These observations, like those in the Kosa et al paper, highlight the important tradeoffs of permanent vascular access placement in hemodialysis patients initiating hemodialysis with a catheter.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…In other work, 2 we found that while vascular access events preceding successful use favor AV grafts, those occurring after successful use favor AV fistulas. These observations, like those in the Kosa et al paper, highlight the important tradeoffs of permanent vascular access placement in hemodialysis patients initiating hemodialysis with a catheter.…”
supporting
confidence: 51%
“…In a comparative national study on elderly HD patients, we found that AV grafts were almost twice as likely as AV fistulas to be successfully used for dialysis within 6 months (adjusted OR, 1.86; 95% CI, 1.73-1.99), an intervention to achieve successful use for dialysis was required more frequently in patients with an AV fistula vs those with an AV graft (OR, 2.66; 95% CI 2.26-3.12) , and patients receiving an AV fistula had a 2-month longer catheter dependence prior to successful use as compared to AV grafts (p <0.001). 2 Taking these issues into consideration, Kosa et al conducted an innovative study comparing the costs of attaining and maintaining patency for AV fistulas as compared to AV grafts among hemodialysis patients. In addition to comparing undifferentiated costs over 1, 3 and 5 years, the authors analyzed AV-access type and risk of failure to mature (FTM) on total costs.…”
mentioning
confidence: 99%
“…Consequently, a significant number of patients, amounting to 18% and 7% of the total haemodialysis population in the USA (USRDS 2017) and Europe (Noordzij et al 2014), respectively, rely on a synthetic arteriovenous graft (AVG) for receiving HD treatment. This percentage might increase in the future, as recent research suggests that, for patients with limited life expectancy, AVGs show fewer complications compared to AVFs (Hall et al 2017;Lee et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical guidelines recommend matured arteriovenous fistula (AVF) as the optimal type of vascular access for hemodialysis patients of all ages. In older dialysis recipients, AVF, once matured, is associated with long‐term benefits of greater patency and requires less interventional procedures to maintain functionality as compared to another type of permanent vascular access, arteriovenous graft (AVG) . Studies, however, show increased age is associated with reduced rate of AVF maturation.…”
Section: Introductionmentioning
confidence: 99%
“…In older dialysis recipients, AVF, once matured, is associated with long-term benefits of greater patency and requires less interventional procedures to maintain functionality as compared to another type of permanent vascular access, arteriovenous graft (AVG). 1 Studies, however, show increased age is associated with reduced rate of AVF maturation. Nationwide, the prevalence of AVF maturation was lower in patients over 75 years (61%) as compared to those 65-74 (64%) and 45-64 (67%).…”
Section: Introductionmentioning
confidence: 99%